Electroencephalography and Epilepsy Course at UH Cleveland Medical Center, Cleveland, Ohio, United States - Park, Jun T.; Devereaux, Michael; Abboud, Hesham; Ashraf, Fareeha; Cohen, Mark; Couce, Marta; DeBrosse, Suzanne; Fastenau, Philip; Vaca, Guadalupe Fernandez-Baca; Garcia-Losarcos, Naiara; Kahriman, Mustafa; Lacuey, Nuria; Marsey, Marge; Miller, Jonathan; Rosen, Carol; Shahid, Asim; Tangen, Rachel; Wien, Michael; Lüders, Hans (Journal of Pediatric Epilepsy, 2019)
Prof. Hans Lüders organized the first International Electroencephalography (EEG)/Epilepsy course in Cleveland (Ohio, United States) in 1979. His vision was to impart a framework of basic knowledge in EEG and epilepsy. The course participants are assumed to have no prior knowledge of EEG or epilepsy. As such, the course is structured and paced to meet the expectations set forth by the organizing committee at the completion of the course. The curriculum has evolved over the years to reflect advancement of the field. There is an added emphasis on semiology (seizure semiology) and epileptic disorders. Also, the course content has expanded to include broader topics such as the intersection between epilepsy and sleep medicine for both adults and children. The course lasts 8 weeks and is offered twice a year, free of charge, in winter and summer at the University Hospital in Cleveland, Ohio, United States. The average class size ranges from 25 to 30, composed of individuals from around the world. The class hours are generally from 8 a.m. to 3:30 p.m. Daily attendance is expected as new concepts quickly build on previous ones. Midterm and final examinations are used for evaluations. Both written and verbal feedbacks on homework assignments are given daily. At the end of the course, a certificate of completion is awarded. The purpose of this article is to discuss the structural details of this intensive educational course that has been offered for 40 years.
Keywords: UH EEG/epilepsy course; UH Cleveland EEG/epilepsy course; electroencephalography and epilepsy course; EEG unknown session; EEG seizure session; seizure semiology session; epilepsy surgical case session; anamnesis session; Hans Lüders; seizure semiology